Students' attitudes and awareness of the reference and information services at the University of the Philippines at Los Baños Library - Tolentino, Noemi G.; Granda, Yolanda C.; David, Lourdes T. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1992)
The study was conducted to determine the students' attitudes and awareness of the reference and information services and awareness of the reference and information services at the University of the Philippines at Los Baños (UPLB) Library. It also assessed the library reference and information services with a view of arriving at measures towards improvement of the services at the UPLB Library
Questionnaires used in data gathering were structured and pretested. A total of 440 undergraduate and graduate students enrolled during the second semester 1991-1992, served as respondents
The findings revealed that undergraduate students were the frequent users of the reference and information services and that there was a very high awareness about the services (97.27 per cent) among the respondents. Almost all of the respondents (77.5 percent) consulted the services for their class assignments and 56.82 percent for completing their term papers. While graduate students were 100 percent aware of the existence of the reference and information services, most of them only fairly knew about the available services (84.74 per cent). Only 12.96 percent fully knew about the said services. The graduate students were more satisfied with their reference and information needs than the undergraduates. About two-thirds of the respondents sought assistance from the librarian or any support staff in their quest for information and almost half of them were satisfied with the assistance provided to them. The services were rated from satisfactory to good. Respondents suggested that reference and information materials be housed in one floor only and that a full-time reference and information librarian be permanently assigned to attend to students' needs
Typescript
Vita.
Thesis (Bachelor of Library Science)
Keywords: Libraries, University and college -- Reference services; University of the Philippines Los Baños Library -- Information service